Doing reasonable hope within a cultural-historical activity framework - Oswald , MM; Perold, MD (South African Journal of Higher Education, 2011)
In this article we present a conceptual framework that we have found sufficiently robust and broad-based to offer a platform for engaging with social and educational challenges in collaboration with our students and research participants. In our framework we employ aspects of the work done by Engeström (1987; 2001) in terms of culturalhistorical activity theory (CHAT), Rule’s (2004) concept of ‘dialogic space’, as well as the notion of ‘doing reasonable hope’ as developed by Weingarten (2007). We present it as our particular effort to make a contribution to reaching the millennium goals. We draw on two of the more prominent conceptual tools offered by Engeström: his mediational triangle and notion of expansive learning, as well as his metaphor of knotworking and show how hopefulness-in-action allows us the scope to maintain that our way of working is centrally about doing reasonable hope.